Оцінка і прогнозування в геоекологічних дослідженнях - Гавриленко, О. П. (Київський національний університет імені Тараса Шевченка, 2017)
Розглянуто застосування оцінювальних і прогнозних методів досліджень в геоекології з метою оцінки придатності геоекосистем або їхніх окремих компонентів для конкретного виду природокористування, а також попередження прояву надзвичайних екологічних ситуацій для забезпечення оптимального функціонування геоекосистем. Проаналізовано наявні різновиди інтегральних і окремих оцінок та доцільність їхнього проведення для потреб оцінювання негативних наслідків господарського впливу на природу як середовища мешкання людини. Розглянуто найбільш розповсюджені методи прогнозування та обґрунтованість їхнього вибору залежно від мети, завдань і терміну прогнозування. Наведено основні послідовні етапи геоекологічного оцінювання і прогнозування.

Geoecology needs evaluative research methods most of all for estimation of the level of geosystems’ properties suitability or their separate components for particular kind of nature management. Integral evaluation is given to the whole natural complex characterized by homogeneity and set of separate kinds of resources. The necessity of receiving separate evaluation marks is caused by the fact that the whole geoecosystem cannot be evaluated without the evaluation of its separate properties, that is without having separate evaluation marks. The demand for general (integral) evaluation erases with the need of choosing one object among a bunch of others by a complex of some properties but not by one separate property. Evaluation of the negative consequences of human impact on nature is based on the detection of changes of nature as human habitat; the main criterion of this evaluation is population health. Usually, estimation of the impacts consequences implies certain gradual steps. Forecast methods for prediction of the development of ecological emergencies is used in geoecology aiming to provide the optimal geoecosystem functioning. In many cases geoecological forecast’s target is to develop the ideas about future geoecosystem, their fundamental properties and diverse changing states first of all caused by human activity. One of the main tasks of that forecast is to prevent possible devastating natural processes that are strengthening by technical instruments, and also create rational territory structure, detect secondary effects and possible long-term environmental changes. Forecast research also aims to produce information about the term of natural resources irreversible exhaustion and environmental digression due to placing of natural using objects. In this case there is a need identify not only the object’s impact on nature, but also environmental functions that are deteriorated because of that impact. Forecast method has to be chosen depending on the aim and tasks of the forecast; term of that forecast; forecast object’s special features; past experience etc. Great diversity of forecast methods leads to the necessity of choosing the most suitable in every particular situation. The result of geoecological forecast has to be the forecast map that displays those geoecosystems with relatively univocally developing anthropological impacts. Geoecosystems displayed on the map can become the main structural units of predicting and environmentally-protecting map in future investigations, which are used for making final project-planning decisions.
Evaluation and forecasting in geoecological research
Keywords: комплексна оцінка території; геоекологічне прогнозування; прогнозна карта; економічна і позаекономічна оцінка; методи прогнозування; comprehensive area’s evaluation; geoecological forecasting; predictive map; economic and non-economic assessment; forecasting methods